The Concept and Effectiveness of Self-Purification in Spirituality from the Perspective of the Sufis: A Literature Review of the Thoughts of Al-Ghazali and Said Hawwa - Moh. Kamil Fikri; Najlatun Naqiyah; Titin Indah Pratiwi; Wiryo Nuryono (G-Couns: Jurnal Bimbingan dan Konseling, 2025)
Every human being yearns for happiness in this world and the hereafter. In today's modern era, technology and science are continually developing, enhancing every human activity. However, not a few in contemporary society experience symptoms of mental health issues, often stemming from the concept of self-purification, which can lead humans to happiness in this world and the hereafter. The purpose of the concept of self-purification is (1) to know yourself, (2) to cultivate positive traits such as self-confidence, patience, gratitude, etc., (3) to live in the world as a worship of Allah SWT. This study uses a library research methodology. The researcher used a descriptive research method. This study analyzed 20 selected articles from Google Scholar, Scopus, and Sciedirect (2017-2024) that focused on the concept of Self-purification in Sufism. The purpose of self-purification is to cleanse the soul from negative behavior. The findings show that self-purification is effective as a spiritual intervention for modern mental problems such as stress and addiction. The conclusion is that the concept of self-purification can have a positive impact on behavioral and cognitive changes. Keywords: the concept of self purification, effectiveness of self purification, spirituality